Perbedaan Intensitas Nyeri Tehnik Pemberian Kompres Air Hangat Dan Aroma Terapi Mawar Pada Ibu Bersalin Kala I Fase Aktif - Dinda Regina Pratjna Pramita; Rahajeng Siti Nur Rahmawati; Sumy Dwi Antono (coba, 2017)
Childbirth pain is common. The onset of pain is due to uterine contractions, the pain felt stronger in the active phase. Management of Childbirth pain with non-pharmacological methods is very helpful for maternal mothers to reduce pain, one of them with the provision of warm water compresses and rose aromatherapy. This study aims to analyze the differences in pain intensity by giving warm water compresses on the lower back and aroma therapy of roses in the maternal mothers when I active phase in BPM Patmi Hartati Kediri Regency. The research design used was Comparative Study 2 paired samples with Pre-test and Post-test. Sampling was conducted from July 28 to August 18, 2017 with a population 27 mothers and simple random sampling technique with a sample of 26 mothers in BPM Patmi Hartatati. There are two groups that will be compared using with pre-test before treatment is given, after that post-test after treatment is given. This research using data analysis Wilcoxon Matched Pairs Test and Mann Whitney U-Test. The Wilcoxon Matched Pairs Test statistic shows that the compresses warm water group with value Tcount (13) < Ttable (17) and aromatherapy groups rose in value Tcount (9) < Ttabel (17) Which means there is a difference in pain intensity before and after treatment. Based on statistical test results Mann Whitney U-Test values obtained Ucount (77) < Utable (39) then it can be said H0 accepted and H1 rejected which is mean there is no difference in the intensity of pain with the provision of warm water compresses on the lower back and aroma therapy rose in maternal mothers when I Active Phase at BPM Patmi Hartati Kediri Regency. Keywords: childbirth pain, warm water compress, rose aromatherapy.